The indian earning couple - role stressors, inter-role conflict and moderation impact of workplace social support - Sreedhar, Volety Naga (Teorija in praksa, 2025)
Due to a lack of support resources, the nature of family and work settings causes Indian earning couples to experience an imbalance while performing their work and family roles. The study developed and tested a model for investigating the moderation impact of two such social support resources in the workplace – supervisor and co-worker – on the inter-role conflict faced by an Indian earning couple. Data were collected and analysed in relation to 676 members of earning couples from 11 major Indian cities using snowball sampling. An interesting finding is that even though both Work Overload (WO) and Family Overload (FO) contribute significantly as role stressors, the individual variable impact created by WO is less effective than FO on inter-role conflict. Although workplace social support showed a moderating effect on inter-role conflict, on the individual variable level co-worker and supervisor support less effectively moderated the inter-role conflict created by FO compared with WO. Practical implications of the study are outlined with respect to business and future research directions.
Keywords: co-worker support; family overload; indian earning couple; indijski par z dvema dohodkoma; inter-role conflict; konflikt med vlogami; podpora nadrejenega; podpora sodelavcev; preobremenjenost z delom; preobremenjenost z družino; role stressors; stresni dejavniki zaradi družbenih vlog; supervisor support; work overload